2016
DOI: 10.3389/feart.2016.00042
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Monsoon Rain and Its Relationship with Monsoon Onset over the Indochina Peninsula

Abstract: We analyzed rainfall during the pre-monsoon season from 1979 to 2002 over the Indochina Peninsula. Our multi-year analysis confirmed that the passage of the upper trough and moisture convergence in the lower troposphere produce intermittent rainfall events during the pre-monsoon season. From this result, three questions are raised. First, what are the characteristics of the upper trough? Second, what is the cause of the significant amount of moisture during the pre-monsoon season over inland Indochina? Third, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…This finding also revolutionizes the idea that the pre-summer rainfall over the Indochina Peninsula is not a localized phenomenon, but rather it is a synoptic-scale phenomenon. Kiguchi et al (2016) confirmed the passage of the upper trough using a longer data set from 1979 to 2002. They further noted that this upper trough is associated with the midlatitude cyclone over the Yangtze River basin and that the rainfall amount during the pre-summer monsoon period has no clear relationship with the onset timing of the summer monsoon over the Indochina Peninsula.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…This finding also revolutionizes the idea that the pre-summer rainfall over the Indochina Peninsula is not a localized phenomenon, but rather it is a synoptic-scale phenomenon. Kiguchi et al (2016) confirmed the passage of the upper trough using a longer data set from 1979 to 2002. They further noted that this upper trough is associated with the midlatitude cyclone over the Yangtze River basin and that the rainfall amount during the pre-summer monsoon period has no clear relationship with the onset timing of the summer monsoon over the Indochina Peninsula.…”
Section: Introductionsupporting
confidence: 55%
“…In general, there are 2,103 days during the pre-summer monsoon period based on the aforementioned conditions. We used the 240 WÁm −2 as the threshold for OLR in depicting the active convection following Kiguchi et al (2016). Values below (above or equal to) this threshold indicates enhanced (suppressed) convection.…”
Section: Methodsmentioning
confidence: 99%
“…As noted previously in Matsumoto (1997) for the rainy season over the Indochina Peninsula, sometimes earlier rainy season onset can be recognized in the Asian monsoon region. As for the rainfall increase in the Indochina Peninsula, Kiguchi and Matsumoto (2005) and Kiguchi et al (2016) attributed to the influence of mid-latitude westerly trough to the occurrence of rainfall before the monsoon circulation onset. On the other hand, Akasaka (2010) and Akasaka et al (2007Akasaka et al ( , 2018, and Moron et al (2009) did not present such discrepancy between the rainy season onset and monsoonal wind changes.…”
Section: Spatial Contrasting Features Of Rainfall and Low-level Cirmentioning
confidence: 99%
“…Kiguchi and Matsumoto (2005) and Kiguchi et al (2016) showed that the passage of the synoptic-scale eastward-moving trough produced the intermittent rainfall in Thailand during the pre-monsoon season. Yokoi et al (2007) showed the predominance of intra-seasonal variations in rainfall over the Indochina Peninsula during the summer monsoon season.…”
Section: Intra-seasonal Variability and Synoptic-scale Influencesmentioning
confidence: 99%